Nrf2 Down-Regulation by Camptothecin Favors Inhibiting Invasion, Metastasis and Angiogenesis in Hepatocellular Carcinoma - Liu, Qian; Zhao, Shanshan; Meng, Fanguang; Wang, Hankang; Sun, Liwei; Li, Guijie; Gao, Feng; Chen, Feng (Frontiers in Oncology, 2021)
Higher oxidant stress capacity could promote invasion and metastasis. Previous study showed hepatocellular carcinoma (HCC) expressed more Nrf2 than para-carcinoma tissue. The chemotherapeutics such as epirubicin (EPI) also increased Nrf2 expression. Camptothecin (CPT) has been found to inhibit tumor growth by down-regulating the key molecule of antioxidant stress signal - Nrf2. But the role of Nrf2 in invasion and metastasis was still unclear. In this study, we use EPI, CPT to determine the invasion and metastasis in Huh7 cells, H22 and Huh7 mouse model. In Huh7 cells, Nrf2 expression and ROS level were found increased after incubation with EPI by western blot and Flow cytometry assay. But when combination of EPI and CPT, inhibition of Nrf2 decrease proliferation, invasion and metastasis, which were investigated by CCK8 assay, wound healing and Transwell assays. In Huh7 and H22 mouse model, EPI promote Nrf2 up-regulation and nucleus translocation, which may inhibited by CPT. Tumor growth was obviously inhibited when single application of EPI or CPT. Combination of EPI and CPT could also inhibit Nrf2 expression, but demonstrated more suppressing effect of tumor growth than EPI. Western blot and immunohistochemical staining study revealed Nrf2 inhibition was benefit in decreasing expression of N-cadherin, MMP9, Snail as well as Twist, and increasing E-cadherin, which were associated with Epithelial–Mesenchymal Transition (EMT). Nrf2 down-regulation promoted lung metastasis of H22 cells in vivo. In addition, H&E staining, immunofluorescence staining of VEGFR suggested angiogenesis of Huh7 and H22 tumor were reduced. In conclusion, down-regulation of Nrf2 demonstrated inhibiting on invasion, metastasis and angiogenesis of hepatoma, which may provide a potential therapy in HCC.